2015
DOI: 10.1136/annrheumdis-2015-eular.3504
|View full text |Cite
|
Sign up to set email alerts
|

AB0529 Population Pharmacokinetics of Atacicept in Systemic Lupus Erythematosus (SLE)

Abstract: BackgroundAtacicept is a recombinant TACI/IgG1-Fc fusion protein that binds and antagonizes the biological activity of the B lymphocyte stimulating factor (BLyS) and a proliferation inducing ligand (APRIL). BLyS and APRIL appear to play a role in the pathogenesis of systemic lupus erythematosus (SLE).ObjectivesThe aim of the analysis was to develop a semi-mechanistic binding population pharmacokinetic (PK) model of atacicept in healthy volunteers (HV) and SLE patients, to characterize the influence of covariat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Atacicept showed evidence of efficacy in SLE in the phase II/III study APRIL-SLE and the phase IIb study ADDRESS II [ 18 , 35 ]. A summary of the PK parameters for atacicept as estimated from data are provided in the Supplementary Information; analysis of three clinical trials with the population PK model for atacicept can additionally be found in [ 37 , 38 ].…”
Section: Example: Ataciceptmentioning
confidence: 99%
“…Atacicept showed evidence of efficacy in SLE in the phase II/III study APRIL-SLE and the phase IIb study ADDRESS II [ 18 , 35 ]. A summary of the PK parameters for atacicept as estimated from data are provided in the Supplementary Information; analysis of three clinical trials with the population PK model for atacicept can additionally be found in [ 37 , 38 ].…”
Section: Example: Ataciceptmentioning
confidence: 99%
“…The structural part of the base model of the present analysis was the same as the previous QSS TMDD model 14,22 . An IIV term for the first‐order K a was included, in addition to those for CL/ F , V c / F , V p / F , and R max , while using a diagonal Ω matrix.…”
Section: Resultsmentioning
confidence: 99%
“…A two‐compartment quasi‐steady‐state (QSS) approximation of the target‐mediated drug disposition (TMDD) binding model with first‐order absorption 20 , 21 had previously adequately described total atacicept concentrations from the phase I and phase II APRIL‐SLE studies. 14 , 22 This model is shown schematically in Figure S1 , together with the differential equations used.…”
Section: Methodsmentioning
confidence: 99%
“…'Total' atacicept concentrations of PK samples were used to build a PK model for atacicept, as described (22) (and manuscript in preparation). Briefly, PK data were collected from double-blind, randomized, placebo-controlled clinical studies in which atacicept (25,75 and 150 mg) was given subcutaneously.…”
Section: Population Pk Modelmentioning
confidence: 99%